Potential clinical application of surface electromyography as indicator of neuromuscular recovery during weaning tests after organophosphate poisoning (2017)
ABSTRACT: This study aimed to explore the usefulness of measuring respiratory muscle activity in mechanically ventilated patients suffering from acute organophosphate poisoning, with a view towards providing complementary information to determine the best time to suspend ventilatory support. Surface electromyography in respiratory muscles (diaphragm, external intercostal and sternocleidomastoid muscles) was recorded in a young man affected by selfpoisoning with an unknown amount of parathion to determine the muscle activity level during several weaning attempts from mechanical ventilation. The energy distribution of each surface electromyography signal frequency, the synchronization between machine and patient and between muscles, acetylcholinesterase enzyme activity, and work of breathing and rapid shallow breathing indices were calculated in each weaning attempt. The work of breathing and rapid shallow breathing indices were not correlated with the failure/success of the weaning attempt. The diaphragm gradually increased its engagement with ventilation, achieving a maximal response that correlated with successful weaning and maximal acetylcholinesterase enzyme activity; in contrast, the activity of accessory respiratory muscles showed an opposite trend.